Mobile-Based Digital Assessment Transforming the Learning Support Efficiency - Junaidah; Ambiyar; Fahmi Rizal (International Journal of Interactive Mobile Technologies (iJIM), 2024)
The digital age has brought great changes in many areas of life, including education. The main change is the use of mobile device systems such as smartphones or tablets that are practical to change the way assessments affect learning efficiency. This paper examines how mobile-based digital assessment systems can improve the effectiveness and efficiency of the assessment process in learning. This paper aims to provide educators with practical guidance for integrating technology into their assessment systems by utilizing available mobile smartphones or tablets and conducting an analysis of the benefits and challenges faced. This study also explores how to maximize the use of smartphones or tablets as a support tool in conducting assessments and can enrich the learning experience of students through faster and personalized feedback. Assist educators in managing assessments in a more structured and measurable way. In addition, recommendations for the effectiveness of smartphone use in supporting the assessment system are also included so that educators can achieve optimal results in the learning process. This study contributes to the educational literature by providing new perspectives on the application of technology and the use of mobile devices to assessment by presenting empirical evidence that supports the effectiveness of assessment application in improving the quality of education.